Development, assessment, and evaluation of laboratory experimentation for a mechanical vibrations and controls course. Issue 4 (October 2019) - Liu, Yucheng; Baker, Francie; He, Wenpei; Lai, Wei
A vibrations and controls course in the Department of Mechanical Engineering at Mississippi State University was reorganized by implementing substantial laboratory experimentation. Team projects were designed and assigned to students asking them to develop vibration and control systems using knowledge and theories learned from lectures. Through those projects, students' problem-solving capacity, hands-on experience, and teamwork skills were fully developed. The developed vibration and control systems will be permanently integrated into the curriculum, based on which a series of lab sessions can be designed to reinforce the concepts and theories covered in lectures and gain practical experience to characterize vibration and control behavior of dynamic systems. Student feedback to a course evaluation questionnaire showed that the renovated course met the learning needs of students by addressing most course goals with respect to ABET learning outcomes. Dependence on costly textbook and role of open educational resources in this class were also discussed.